Sugammadex for reversing neuromuscular blockages after lung surgery: A systematic review and meta-analysis. Issue 39 (30th September 2022) - Yang, Jia-Li; Chen, Kuen-Bao; Shen, Mei-Ling; Hsu, Wei-Ti; Lai, Yu-Wen; Hsu, Chieh-Min
Abstract : Background: This study determined whether sugammadex was associated with a lower risk of postoperative pulmonary complications and improved outcomes in lung surgeries. Methods: A systematic literature search was conducted using PubMed, Embase, Web of Science, and the Cochrane Library from January 2000 to March 2022. The characteristics of lung surgeries using sugammadex treatment compared with control drugs and postoperative outcomes were retrieved. The primary outcome was estimated through a pooled odds ratio (OR) and its 95% confidence interval (CI) was identified using a random-effects model. Results: From 465 citations, 7 studies with 453 patients receiving sugammadex and 452 patients receiving a control were included. The risk of postoperative pulmonary complication (PPCs) was lower in the sugammadex group than in the control group. Also, it showed that the effect of sugammadex on PPCs in the subgroup analysis was significantly assessed on the basis of atelectasis or non-atelectasis. Furthermore, subgroup analysis based on the relationship between high body mass index (BMI) and PPCs also showed that sugammadex had less occurrence in both the high BMI (defined as BMI ≥ 25) and low BMI groups. No difference in length of hospital stay (LOS) between the two groups was observed. Conclusion: This study observed that although reversing neuromuscular blockages with sugammadex in patients undergoing thoracic surgery recorded fewer PPCs and shorter extubation periods than conventional reversal agents, no difference in LOS, postanaesthesia care unit (PACU) stay length and chest tube insertion duration in both groups was observed.